Perception of Lean Adoption among Emergency Department Personnel in Public Hospitals in Selangor, Malaysia - Mohamad Jamil, Azizul Rahman; Abdul Manaf, Mohd Rizal; Wan Puteh, Sharifa Ezat; Balakrishnan, Kiran Ganesh (UI Scholars Hub, 2024)
Background: This research aims to assess the perceptions of the staff working in emergency departments in Selangor, Malaysia, regarding the adoption of lean management and identify the factors that affect their perceptions. Methods: A cross-sectional study using the Lean in Healthcare Questionnaire was conducted with 251 respondents, which consisted of doctors, nurses and medical assistants employed in three selected hospitals. Results: One-way analysis of variance (ANOVA) showed a significant difference in every domain score in accordance with the occupation category. For the domain process, a significant negative correlation was found between age and domain score (r = –0.195, p = 0.002). In particular, nurses had better perceptions of lean adoption compared with others (odds ratio [OR] = 2.44, p < 0.004). The odds of having a better perception decreased by 6.3% as the age increased (p < 0.008). Conclusions: The findings revealed that age and occupation appeared to be determinants of lean adoption perceptions among emergency department personnel. Specifically, older employees tend to have negative perceptions, while nurses have more positive perceptions. However, further research is needed to understand perceptions of lean adoption better and develop guidelines for implementing lean principles in healthcare settings.